ACADEMIC BRANDING: Individual and Institutional Perspectives - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
Branding occurs in the business world and non-business (social, cultural, political, etc.). Branding is not only useful in the professional realm but also academically. In short, branding has intruded on almost all fields of postmodern community work. This article elaborates on branding in the academic sphere, whose needs are progressively pressing amid increasingly fierce competition. By interviewing academic actors and stakeholders, we construct and examine academic branding dimensions from two perspectives: individual and institutional. From an individual perspective, academic branding works on the aspects of scientific profiles, scientific activities, scholarly works, scientific recognition, and scientific achievements. Meanwhile, academic branding embodies the portfolio dimensions of research, education, and community service activities from the institutional perspective. Academic branding impacts an educational organization's reputation and credibility and contributes to the scholars' personal branding performance and organizational branding in which the scholars ensconce. PEMEREKAN AKADEMIS: Perspektif Individual dan InstitusionalPemerekan tidak hanya terjadi di dunia bisnis, tetapi juga non-bisnis (sosial, budaya, politik, dan lain-lain). Pemerekan tidak hanya bermanfaat di ranah profesional, tetapi juga akademis. Pendek kata, pemerekan telah mengintrusi hampir segenap bidang pekerjaan masyarakat pascamoderen. Artikel ini mengelaborasi pemerekan pada ranah akademis, yang kebutuhannya semakin mendesak di tengah kompetisi yang semakin ketat. Dengan mewawancarai berbagai aktor akademis dan pemangku kepentingan, artikel ini menelaah dimensi-dimensi pemerekan akademis dari dua perspektif, yakni individual dan institutional. Dari perspektif individual, pemerekan akademis memiliki dimensi Karya-Karya Saintifik, Profil Saintifik, Aktivitas Saintifik, Pengakuan Saintifik, dan Prestasi Saintifik, sedangkan dari perspektif institutional, pemerekan akademis mewujud dalam dimensi portfolio kegiatan Penelitian, Pendidikan, dan Pengabdian Kepada Masyarakat. Pemerekan akademis atau academic branding tidak hanya berdampak pada reputasi dan kredibilitas organisasi akademis, tetapi juga berkontribusi pada performa baik pemerekan personal akademisi maupun organisasi tempat akademisi tersebut bernaung. To cite this article (7th APA Style): Wijaya, B. S. (2016). Academic Branding: Individual and Institutional Perspectives. Journal Communication Spectrum: Capturing New Perspectives in Communication, 6(1), 44-59